A Spatial Decision Support System Approach to a Flexible Physical Development Planning of the Obafemi Awolowo University Estate - Baloye, David Olutunji (2015)
The study assessed the present state of physical development of the Obafemi Awolowo University estate and developed a spatial decision support framework for capturing physical development on the university estate. It also provided a model for physical expansion scenarios of the university on the basis of a range of parameters including access roads, residential accommodation, lecture theaters and services spaces. This was with a view to evolving a system that could assist the physical development plans of the university to respond flexibly and effectively to unanticipated land use demand.